(untitled) (Research, Society and Development, 2020)
Objective: to understand the self-care strategies used by users of a Psychosocial Care Center - Mode II. As a social relevance, it aims to enable critical reflections in the academic-professional sphere about the participation of people with mental disorders as co-authors of the health-disease-care process itself, seeking to contribute to the rupture of the traditional biomedical and psychiatric model. Methodology: This is a qualitative research, exploratory-descriptive. CAPS II users participated in the research, with data collected through semi-structured interviews from July to August 2018 and analyzed according to the Discourse Analysis method. Results: there are categories arising from the narratives of eight users, five female and three male. An arsenal of self-care strategies used by service users emerged, in line with the principles of autonomy, protagonism, intersubjectivity, co-responsibility and co-management in health production, which denote the constitution of new modes of subjectification. Conclusion: Although there is a need for transformations in practices still based on the medicocentered model, the results showed that CAPS has been working in a strategic way, favoring the creation of social bonds and providing a basis for the construction of self-care practices.